Detecting Financial Statement Fraud Using Hexagon Theory: The Role of Effective Monitoring - Retno Wulansari; Rr. Sri Handayani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This study investigates the application of the fraud hexagon theory in detecting financial statement fraud and examines effective monitoring as a moderating variable. Method - This research focuses on companies in the Consumer Cyclicals sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Logistic regression analysis was conducted using EViews 13. Main Findings - The results show that financial targets and board duality drive financial statement fraud. Industry characteristics, auditor turnover, director turnover, and director arrogance do not have a significant effect. The audit committee serves as a monitoring mechanism that can weaken the influence of financial targets, director arrogance, and board duality on financial statement fraud but is ineffective in mitigating the impact of other factors. Theory and Practical Implications - These findings highlight the importance of strengthening corporate governance with strict oversight of financial targets and board duality. This research can be used by companies and investors to identify fraud using elements of Hexagon Theory. Novelty - This study advances previous research by introducing effective monitoring as a moderating variable in the relationship between fraud hexagon elements and financial statement fraud.